A traffic surveillance function and conflict detection method for runway manoeuvres - Sammut, Andrew; Zammit, Brian; Zammit-Mangion, David (American Institute of Aeronautics and Astronautics (AIAA), 2012)
Runway conflicts continue to occur regularly in commercial aviation. There have been several initiatives worldwide to implement new systems capable of detecting such conflicts. For example, ground based systems have been implemented in several airports improving the air traffic controller situational awareness. Unfortunately, however, these systems fail to provide support in situations where the time to conflict is very short. This paper discusses the implementation of an algorithm for traffic surveillance and runway conflict detection on board the aircraft to provide the necessary information directly to the crew. The rules on which the detection algorithm is based and the alert suppression logic to reduce the number of nuisance alerts are discussed. A description of the multi-threaded software architecture is also included.